Association between psychological distress and health risk behaviours among youth in Karachi - Nourina; Aiesha Ishaque (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the frequency of psychological distress and its association with health risk behaviours among youth in an urban setting. Method: The cross-sectional study was conducted from May to September 2023 at the Indus University of Health Sciences, Karachi, and comprised individuals of either gender aged 15-24 years. Psychological distress was assessed using the Kessler 10+ scale and health risk behaviours were evaluated using a structured questionnaire covering dietary habits, drug abuse, hygiene, physical activity, tobacco use, violence, and unintentional injury. Data was analysed using SPSS 26. Results: Of the 455 individuals approached, 391(85.9%) were included; 237(68.9%) females and 107(31.1%) males. The median age of the participants was 21 years (interquartile range: 19-22 years). The overall median score for psychological distress was 24 (interquartile range: 19-30), with 285(72.9%) participants reporting psychological distress. Psychological distress had significant association with mother’s education (adjusted odds ratio: 0.28, 95% confidence interval: 0.1-0.77) and university bullying (adjusted odds ratio: 8.01, 95% confidence interval: 2.4-26.71). Conclusion: The prevalence of psychological distress among the young subjects was high. Efforts aimed at addressing bullying in educational settings is critical for mitigating psychological distress. Key Words: Adolescent, Logistic models, Health risk, Tobacco use, Substance-related disorders, psychological distress.